Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together untuk Meningkatkan Hasil Belajar Siswa Kelas IV pada Materi Soal Cerita Bilangan Bulat di SD Terpadu Negeri Nafar - Yamrat, Elias Jat Rafel; Takaria, J.; Ishabu, La Suha (Universitas Pattimura, Program Studi Diluar Kampus Utama (Program Studi Pendidikan Guru Sekolah Dasar), 2022)
The main problem in this research is the low learning outcomes of fourth grade students of SD Negeri Nafar in Mathematics. One of the factors causing low student learning outcomes is the lack of variant models or methods used by teachers in teaching. This type of research is classroom action research (CAR) which is carried out in two cycles, each cycle includes planning, implementation, observation and reflection. by applying the Numbered Head Together type of cooperative learning model. The subjects of the study were the fourth grade students of SD Negeri Nafar, totaling 12 people. The benefit of this research is that the results of this study can add insight and experience on how to learn mathematics by using Number Head Together (NHT) learning. In addition, it can provide an increase in the quality of learning through the NHT learning model. The type of data collected is qualitative data in the form of observations of student activities and the teacher during the teaching-learning process, and quantitative data in the form of student learning outcomes through the final action evaluation test. The results of the first cycle obtained learning mastery with a percentage of 59%. Furthermore, in the second cycle, 83% mastery was obtained. Based on the research indicators, it can be concluded that the application of Numbered Head Together type of cooperative learning model can improve mathematics learning outcomes for Grade IV SD Negeri Nafar.